Pengaruh Pelayanan Administrasi Kependudukan Dan Kinerja Pegawai Terhadap Kepuasan Masyarakat Di Kelurahan Cigugur Tengah - Nurhalimah, Ajeng Pipih; Takwim, R Iim; Mulawarman, Aditia (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2023)
Service is the key to success in various service activities or businesses. Its role is very large in efforts to provide satisfaction to the community. The public can directly assess government performance based on the quality of public services which are in the interests of many people and the impact is directly felt by people from all walks of life. This study aims to determine the effect of the Community Satisfaction Survey on the Improvement of Population Administration Services in Cigugur Tengah Village. The method used is quantitative research with a population and sample of people who have surveyed community satisfaction in the Cigugur Tengah Village. Based on the results of the research and the results of the research analysis on the effect of the community satisfaction survey on improving population administration services in Cigugur Tengah Village, it was shown that the community satisfaction survey had an effect on improving population administration services in Cigugur Tengah Village. The results of this study 0.806 or 80,6% community satisfaction is influenced by administrative service variables and employee performance and is influenced by other variables not present in this study of 19,4%.